2019
DOI: 10.5334/aogh.2452
|View full text |Cite
|
Sign up to set email alerts
|

The Road User Behaviours of Chinese Adolescents: Data From China and a Comparison With Adolescents in Other Countries

Abstract: Objectives: Adolescents experience high rates of road traffic injuries and deaths as pedestrians and cyclists. One likely reason for adolescents’ elevated traffic injury risk is their risky behaviour on the road. This study examined Chinese adolescents’ road behaviour using a nationwide survey. Methods: Across 7 Chinese provinces, 4,794 adolescents completed the Chinese version of the Adolescent Road User Behaviour Questionnaire (ARBQ). Results from t-tests and ANOVAs d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…The first aim of this study was to verify sex-related differences in adolescents’ frequency of MVCs. Previous studies have reported conflicting results, with some studies finding a higher prevalence among adolescent males [ 4 , 14 , 15 , 16 ], but research reports few and inconsistent results concerning females and road accidents [ 95 ]. However, our study is in line with recent studies by Breen and colleagues [ 4 ] and by Le and colleagues [ 5 ], which evidence a greater risk of recurrent MVCs for adolescent males than females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first aim of this study was to verify sex-related differences in adolescents’ frequency of MVCs. Previous studies have reported conflicting results, with some studies finding a higher prevalence among adolescent males [ 4 , 14 , 15 , 16 ], but research reports few and inconsistent results concerning females and road accidents [ 95 ]. However, our study is in line with recent studies by Breen and colleagues [ 4 ] and by Le and colleagues [ 5 ], which evidence a greater risk of recurrent MVCs for adolescent males than females.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies on adolescents’ road collisions have reported a rate of prevalence of approximately of 50% [ 7 , 8 , 9 ], with important consequences for their psychological and physical well-being [ 10 , 11 , 12 ]. Most studies have shown a higher prevalence of injuries and road accidents among males [ 13 , 14 , 15 , 16 , 17 ], and results concerning females in relation to road accidents are few and inconsistent [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research based on simulated roads carried out in the USA where 85 children and 26 adults were observed in the same traffic conditions while crossing the road, pointed out that younger children, boys and children with less behavioral control engaged in risker behavior [11]. Recently, studies regarding the influence of children's age and gender on their traffic behavior were carried out also in China [12,13] and Estonia [14]. Results from the study [12] suggested that male adolescents reported riskier behaviors than female and showed significant age difference-older adolescents demonstrated riskier behavior than younger; however, the other study established that there is no statistically important difference between male and female population regarding risky traffic behavior [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies regarding the influence of children's age and gender on their traffic behavior were carried out also in China [12,13] and Estonia [14]. Results from the study [12] suggested that male adolescents reported riskier behaviors than female and showed significant age difference-older adolescents demonstrated riskier behavior than younger; however, the other study established that there is no statistically important difference between male and female population regarding risky traffic behavior [13]. In a study carried out in Estonia, the gender factor was important, and on average 13-year-old boys take more risks as pedestrians than girls [14].…”
Section: Introductionmentioning
confidence: 99%